Competing Constitutional Rights: Developing the Canadian Approach - Oatway, Catherine (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2025)
When the state limits a right protected by the Canadian Charter of Rights and Freedoms (Charter), it must demonstrate that the limitation is justified in a free and democratic society. However, in certain circumstances a Charter right may also be limited by the valid simultaneous exercise of another individual’s rights. To address these situations, Canadian courts have developed a test similar to the Oakes framework that asks: First, whether the rights conflict or overlap at all; second, if that conflict can be overcome by alternative, accommodating measures; and, if not, third, whether the proposed approach strikes a rights-respecting balance. But when they reach the third stage there is a palpable risk that they will conduct an improper balancing inquiry wherein the effects of denying one right are weighed against protecting the other, rather than the effects of limiting the right(s). Instead, if the exercise of both rights creates a true competition which cannot be accommodated, courts must reconcile the claims: They must redefine the strength of each right relative to the other’s competing claims, to the broader factual matrix, and to the Charter’s interpretative guidelines, with the objective of facilitating the meaningful exercise of both rights. A balancing inquiry is only appropriate to the extent that it assesses whether the limitations (i.e., the results of the reconciliation analysis) are proportionate.